Changes of Radiation Treatment Concept Based on 68Ga-PSMA-11-PET/CT in Early PSA-Recurrences After Radical Prostatectomy - Bottke, Dirk; Miksch, Jonathan; Thamm, Reinhard; Krohn, Thomas; Bartkowiak, Detlef; Beer, Meinrad; Bolenz, Christian; Beer, Ambros J.; Prasad, Vikas; Wiegel, Thomas (Frontiers in Oncology, 2021)
Background and purpose. Salvage radiotherapy (SRT) is the main potentially curative treatment option for prostate cancer patients with post-prostatectomy PSA progression. Improved diagnostics by positron emission tomography / computed tomography (PET/CT) can lead to adjustments in treatment procedures (e.g. target volume of radiotherapy, androgen deprivation therapy). We analyzed the impact of 68Ga-PSMA-11-PET/CT on the target volume in early biochemical recurrence (PSA up to 0.5 ng/ml). Patients and methods. We retrospectively analyzed 76 patients with biochemical recurrence after radical prostatectomy in whom SRT was planned after 68Ga-PSMA-11-PET/CT. All patients had a PSA ≤0.5 ng/ml. An experienced radiation oncologist determined the radiotherapy concept, first with consideration of the PET/CT, second hypothetically based on the clinical and pathological features excluding PET/CT results. Results. Without considering the PET/CT, all 76 patients would have been assigned to RT, 60 (79%) to the bed of the prostate and seminal vesicles alone, and 16 (21%) also to the pelvic lymph nodes because of histopathologic risk factors. Uptake indicative for tumor recurrence in 68Ga-PSMA-11-PET/CT was found in 54% of the patients. The median pre-PET/CT PSA level was 0.245 ng/ml (range 0.07 – 0.5 ng/ml). The results of the PET/CT led to a change in the radiotherapeutic target volume in 21 patients (28%). There were major changes in the target volume including the additional irradiation of lymph nodes or the additional or exclusive irradiation of bone metastases in 13 patients (17%). Minor changes including the additional irradiation of original seminal vesicle (base) position resulted in 8 patients (11%). Conclusion. Using 68Ga-PSMA-11-PET/CT for radiation planning, a change in the treatment concept was indicated in 28% of patients. With PET/CT, the actual extent of the tumor can be precisely determined even with PSA values of ≤0.5 ng/ml. Thus, the treatment concept can be improved and individualized. This may have a positive impact on progression free survival. Our results warrant further prospective studies.